Getting proportionality in perspective: philosophy, history, and institutions - Lacey, Nicola (Crime and justice, 2021)
Conceptual debates about proportionality and its moral and political force need to be placed in historical and institutional context. Conceptual, moral, political, and practical questions about proportionality are inextricably linked. This insight should lead us away from the dominant conception of proportionality as a moral precept and toward a political conception of proportionality that is inevitably shaped by prevailing conceptions of what proportionality is for and, in modern democracies, is grounded in democratic practices and the institutional structures of democratic states. This insight has important implications for the prevailing disciplinary division of labor, calling into question the tendency to separate conceptual and philosophical from social theories of punishment. It is important to try to understand the conditions under which stable constraints on the state’s power to punish, and accountability mechanisms adequate to guaranteeing the fittingness of punishment by reference to democratically endorsed standards—which seem to be the key animating concerns of contemporary appeals to proportionality—are most likely to be realized, and conversely where they are likely to be most under threat. This is both an important issue in itself, and a case study in the interaction between concept and context.